Pengolahan koleksi di Taman Baca Masyarakat Karya Mulya Kota Palembang dalam upaya meningkatkan temu kembali informasi - Sely Yoanda; Aang Gunaidi (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction. The number of collections at the Karya Mulya Community Reading Center or Taman Bacaan Masyarakat (TBM) Palembang City continue to increase. It is necessary to evaluate the collection the efficient collection management that will influence information retrieval and increase public interest in reading. Data Collection Methods. This study used a qualitative research method with a descriptive approach. Data Analysis. The data analysis was conducted descriptively through several stages including data reduction, data presentation, and conclusion/data verification. Results and Discussion. TBM Karya Mulya Palembang City has not carried out a systematic collection processing. The current stages of collection processing at TBM Karya Mulya Palembang City consist of inventorying, classifying children, adolescents and adults reading books, stamping collections, and shelving. This evaluation in a collection processing model at TBM Karya Mulya Palembang City lead to the better collection management based on library collection processing standards. Conclusion. The TBM collection processing model of Karya Mulya Palembang City can be a reference in collection processing to facilitate information retrieval.